PERAN KEGIATAN JUM’AT AGAMIS DALAM MENINGKATKAN SPIRITUALITAS DI SEKOLAH MENENGAH KEJURUAN - Ummu Salma Nur Tsania; Jumari Jumari (JURNAL ILMIAH NUSANTARA, 2025)
Religious activities in schools are a strategic effort to shape character and enhance students' spirituality. This article discusses the role of "Religious Friday" activities routinely implemented at SMKN 1 Jombang as a means of fostering students’ spiritual awareness. These activities include the recitation of Surah Yasin, tahlil, sholawat, and istighotsah, guided by Islamic education teachers. This study employs a qualitative approach using a case study method, with data collected through interviews, observation, and documentation. The results indicate that Religious Friday activities contribute positively to developing students’ religious behavior, discipline in worship, and the internalization of values such as sincerity, responsibility, and social care. Furthermore, active teacher involvement and a supportive school environment are essential factors in the program’s success. Therefore, Religious Friday activities are not merely ceremonial routines but serve as an effective instrument in nurturing and strengthening students’ spirituality within the school context.